Prognostic impact of dimensional factors in pT1 gastric cancer. (September 2021) - Kunisaki, Chikara; Takahashi, Masazumi; Sato, Sho; Tsuchiya, Nobuhiro; Watanabe, Jun; Sato, Tsutomu; Takeda, Kazuhisa; Tanaka, Yusaku; Kasahara, Kohei; Kosaka, Takashi; Akiyama, Hirotoshi; Endo, Itaru
Abstract: Background: The significance of the dimensional factors (tumor diameter, area and volume) as the prognostic factor has not been precisely evaluated in pT1 gastric cancer. Objectives: This study aimed to identify the clinical impact and to confirm the clinical feasibility of the dimensional factors as prognostic factors in pT1 gastric cancer. Methods: We analyzed prognostic factors for disease-specific survival (DSS), overall survival (OS) using clinicopathological factors by univariate and multivariate analyses and the pattern of recurrence in 2011 pT1 gastric cancer (mucosal and submucosal cancers) undergoing R0 gastrectomy. The cut-off values of each dimensional factor was decided by the ROC curve. Results: Cox proportional hazard regression model showed that older age ( ≥ 75) and more advanced pN stage were adverse independent prognostic factors for DSS, and revealed that older age (≥75), greater preoperative co-morbid diseases, proximal and total gastrectomy, operative method and Clavien-Dindo classification (≥grade III) were independent adverse factors for OS. Any dimensional factors were not independent prognostic factors for any survival. Conclusions: The dimensional factors do not influence both OS and DSS in pT1 gastric cancer patients and so it is difficult to apply these dimensional factors for conducting therapeutic strategies. Highlights: The dimensional factors (tumor diameter, area and volume) do not influence both OS and DSS in pT1 gastric cancer patients and so it is difficult to apply these dimensional factors for conducting therapeutic strategies. The dimensional factors do not influence OS and DSS. These factors have no efficacy for conducting therapeutic strategies.